2016
DOI: 10.7150/jca.14549
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression Is Associated with Tumor FOXP3+ Regulatory T-Cell Infiltration of Breast Cancer and Poor Prognosis of Patient

Abstract: Background: Expression of PD-L1 has been estimated to predict the therapeutic potential of PD-L1 inhibition in solid tumors. Recent studies have demonstrated that PD-L1 plays a critical role in regulatory T-cell (Treg) development and functional maintenance. Although increases in FOXP3+Treg infiltration and PD-L1 expression have been revealed in several malignancies, their correlation in human breast tumors is as yet unclear.Methods: Whole-tissue sections from 501 patients with breast cancer were examined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
6
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 52 publications
12
127
6
7
Order By: Relevance
“…However, FOXP3-positive Tregs42 43 are able to suppress immune attack against tumour cells by inhibiting CD4, CD8, natural killer (NK) cell, B cell and antigen-presenting cell function 44 45. FOXP3 counts have additionally been shown to work synergistically with programmed death-ligand 1 (PDL1),46 which is induced in EBV-positive NPC by latent membrane protein 1 (LMP1) through oncogenic pathways and immune modulation 47. Thus, FOXP3-positive Tregs are hypothetically associated with poor prognosis, and thus contradicting the results of this study.…”
Section: Discussioncontrasting
confidence: 80%
“…However, FOXP3-positive Tregs42 43 are able to suppress immune attack against tumour cells by inhibiting CD4, CD8, natural killer (NK) cell, B cell and antigen-presenting cell function 44 45. FOXP3 counts have additionally been shown to work synergistically with programmed death-ligand 1 (PDL1),46 which is induced in EBV-positive NPC by latent membrane protein 1 (LMP1) through oncogenic pathways and immune modulation 47. Thus, FOXP3-positive Tregs are hypothetically associated with poor prognosis, and thus contradicting the results of this study.…”
Section: Discussioncontrasting
confidence: 80%
“…Thus, it plays an important role in dampening the T cell mediated anti-tumor immune response [1,2]. Numerous studies have shown that many human cancers display PD-L1 over-expression, and that its expression is significantly associated with patients' clinical parameters and postoperative prognoses [3][4][5]. In addition, multiple clinical studies have demonstrated that PD-L1 blockade can significantly inhibit tumor progression and improve patient prognosis in many advanced cancers, including melanoma, gastric cancer, non-small-cell lung cancer, ovarian cancer, renal cell cancer and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[100] High levels of Treg cells correlate with cancer progression and poor patient prognosis. [101, 102] Most studies using NPs loaded with drugs, small molecules, oligonucleotides, immunomodulatory compounds, etc. have not directly targeted Treg cells but have indirectly decreased or increased Treg cell levels.…”
Section: Breaking Transport Barriers To Enhance Cancer Immunotheramentioning
confidence: 99%